Effect of peroxymonosulfate oxidation activated by powdered activated carbon for mitigating ultrafiltration membrane fouling caused by different natural organic matter fractions. (April 2019) - Cheng, Xiaoxiang; Li, Peijie; Zhou, Weiwei; Wu, Daoji; Luo, Congwei; Liu, Wenchen; Ren, Zixiao; Liang, Heng
Abstract: Powdered activated carbon (PAC) adsorption has been widely applied prior to ultrafiltration membrane for potable water production. However, the impact of PAC adsorption on membrane fouling was still controversial. To solve this problem, combined PAC and peroxymonosulfate (PMS) pretreatment was proposed in this study. The application of PAC/PMS for mitigating membrane fouling by natural organic matter (NOM) has been evaluated, and compared with PMS oxidation or PAC adsorption alone. The influence of NOM fractions on the control efficiency was also investigated using humic acid (HA), bovine serum albumin (BSA), sodium alginate (SA), and their mixture (HA-BSA-SA). The performance was examined through normalized flux decline, fouling resistances analysis, scanning electron microscopy, and model fits. The results indicated that PAC and PMS exhibited a remarkable synergistic effect in the reduction of NOM, with the DOC reduction rates of 53.6%, 24.3%, 27.1% and 31.4% for HA, BSA, SA and HA-BSA-SA, respectively. PAC adsorption exhibited limited influence on mitigating membrane fouling, and the co-existence of PAC and HA even exacerbated fouling due to the synergistic fouling effect between them. By contrast, PAC/PMS pretreatment efficiently reduced both reversible and irreversible fouling resistances. The control efficiency was closely associated with the NOM fractions in the feed water, and followed the order of SA > HA-BSA-SA > BSA > HA. The fouling mitigation by PAC/PMS was attributed to both PAC adsorption and oxidation with SO4 − and OH. The experimental results are expected to provide a feasible strategy of PAC/PMS for fouling mitigation, and simultaneously solve the problem faced by PAC adsorption. Graphical abstract: Image 1 Highlights: PAC/PMS pretreatment was used to control UF fouling by different NOM fractions. PAC adsorption exhibited limited influence on membrane fouling control. PAC/PMS showed significantly higher control efficiency than PAC or PMS alone. The control efficiency of PAC/PMS was closely associated with the NOM fractions. The presence of PAC in the feed reduced the efficiency of PAC/PMS.